Tumor-activated neutrophils promote metastasis in breast cancer via the G-CSF-RLN2-MMP-9 axis - Sheng, Youjing; Peng, Weidong; Huang, Yan; Cheng, Lanqing; Meng, Ye; Kwantwi, Louis Boafo; Yang, Jiezhen; Xu, Jiegou; Xiao, Han; Kzhyshkowska, Julia; Wu, Qiang (Journal of leukocyte biology, 2023)
The immune component of the tumor microenvironment is essential for the regulation of cancer progression. In breast cancer (BC), a patient's tumor mass is frequently infiltrated by neutrophils (tumor-associated neutrophils, TANs). Our study addressed the role of TANs and their mechanism of action in BC. Using quantitative IHC, ROC, and Cox analysis, we demonstrated that a high density of TANs infiltrating the tumor parenchyma was predictive of poor prognosis and of decreased progression-free survival of patients with BC, who underwent surgical tumor removal without previous neoadjuvant chemotherapy, in 3 different cohorts: training, validation, and independent cohorts. Conditioned medium from human BC cell lines prolonged the lifespan of healthy donor neutrophils ex vivo. Neutrophils activated by the supernatants of BC lines demonstrated an increased ability to stimulate proliferation, migration, and invasive activity of BC cells. Cytokines involved in this process were identified using antibody arrays. The relationship between these cytokines and the density of TANs was validated by ELISA and IHC in fresh BC surgical samples. It was determined that tumor-derived G-CSF significantly extended the lifespan and increased the metastasis-promoting activities of neutrophils via the PI3K-AKT and NF-κB pathways. Simultaneously, TAN-derived RLN2 promoted the migratory abilities of MCF7 cells via PI3K-AKT-MMP-9. Analysis of tumor tissues from 20 patients with BC identified a positive correlation between the density of TANs and the activation of the G-CSF-RLN2-MMP-9 axis. Finally, our data demonstrated that TANs in human BC have detrimental effects, supporting malignant cell invasion and migration.
Online veröffentlicht: 18. Januar 2023
Gesehen am 02.10.2024